OS “PRIVILEGIADOS” DA PRIVATIZAÇÃO: a contrarreforma previdenciária dos servidores públicos no Brasil - Thais Soares Caramuru (Universidade Federal do Maranhão, 2018)
The current capitalist attack to the pensions of Brazilian workers is promo- ted by the discourse of confronting the supposed “privileges” of public ser vers. In sight of this, this article had the general aim of proposing a critical analysis of this argument and, as a speciﬁc target, it intended to point that the counter-reform of public servers’ pensions is a mechanism of expansion of the so called “private pensions”, generating a dialectical relationship between the counter-reform and privatization. Under de auspices of the Marxist theoretical and methodological perspective, the article conﬁrms the hypothesis that the “privileges” rethoric is extremely functional to capital, because it promotes the fragmentation of the working class, hides the fact that the capitalists are the real privileged of the public fund and conceals the interest in privatization.